2016
DOI: 10.1089/lgbt.2015.0096
|View full text |Cite
|
Sign up to set email alerts
|

Cancer's Margins: Trans* and Gender Nonconforming People's Access to Knowledge, Experiences of Cancer Health, and Decision-Making

Abstract: Purpose: Research in Canada and the United States indicates that minority gender and sexuality status are consistently associated with health disparities and poor health outcomes, including cancer health. This article investigates experiences of cancer health and care, and access to knowledge for trans* and gender nonconforming people diagnosed with and treated for breast and/or gynecologic cancer. Our study contributes new understandings about gender minority populations that will advance knowledge concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 62 publications
4
104
0
Order By: Relevance
“…Several gaps in content areas readily covered in other disparity populations, including experiences of health care discrimination, access to care, and stigma, have received little research attention for SGM cancer populations, despite the inclusion of SGM as a health disparity population . Nearly all the research in this review covered SM, not GM (transgender, nonbinary gender) groups; this is a major gap in the literature, as has been previously suggested . In addition, construct development and measurement of topics salient to cancer survivors have not been fully explored in the SGM population .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several gaps in content areas readily covered in other disparity populations, including experiences of health care discrimination, access to care, and stigma, have received little research attention for SGM cancer populations, despite the inclusion of SGM as a health disparity population . Nearly all the research in this review covered SM, not GM (transgender, nonbinary gender) groups; this is a major gap in the literature, as has been previously suggested . In addition, construct development and measurement of topics salient to cancer survivors have not been fully explored in the SGM population .…”
Section: Discussionmentioning
confidence: 94%
“…Of the studies that listed sources of funding, the most commonly cited sources were the National Institutes of Health (n = 5), the American Cancer Society (n = 3), and the Susan G. Komen Foundation (n = 4). In total, 7 studies reported on GM status: 5 studies collected GM status and combined those individuals with SMs, 1 additional study included GMs as a distinct group, and 1 study focused on transgender and gender‐nonconforming patients …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRCA testing was performed in three cases; all tested negative . Thirteen transmen had been taking androgens for 1–15 years . Eight of these transmen had also undergone a mastectomy …”
Section: Resultsmentioning
confidence: 99%
“…Cross‐sectional studies and case reports . Five cases of ovarian cancer were reported, three in case reports and two in a cross‐sectional study . Three of these transmen had taken gender‐affirming hormones for 1–18 years .…”
Section: Resultsmentioning
confidence: 99%